2020
DOI: 10.1111/rec.13179
|View full text |Cite
|
Sign up to set email alerts
|

The role of organic amendments in wetland restorations

Abstract: At the present rate of loss (since 1990), half of the remaining wetlands worldwide will be developed within ~140 years, underscoring the importance of improving the creation and restoration of wetlands. Organic amendments are sometimes used during wetland creation. To evaluate the effectiveness of adding organic amendments we used a combined numerical method to assign “scores” on five categories of evaluation metrics: plant growth, soil properties, carbon accrual, denitrification, and anaerobic processes (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 92 publications
(100 reference statements)
0
14
0
Order By: Relevance
“…Here we address several considerations for preparing a wetland for revegetation. Prior to these actions, appropriate site manipulations are imperative, such as surface contouring and excavation of sites to expose seed banks; removal of subsurface drainage tiles and plugging of drainage ditches to restore hydrology; management of invasive species to alleviate biotic pressures; improving soil conditions through additions of topsoil, organic matter, mulch, lime (to raise pH), fertilizers (if nutrient impoverished), and carbon (if nutrient enriched); inoculation with soil microbes; and soil ripping, disking, or tilling to overcome soil compaction (Galatowitsch and van der Valk, 1994;Vivian-Smith and Handel, 1996;Boyer and Zedler, 1998;Allen et al, 2001;Holguin et al, 2001;Anderson and Cowell, 2004;Daniels et al, 2005;Sutton-Grier et al, 2009;Larson et al, 2019;Scott et al, 2020). We focus here on the next steps following site manipulation: removal of invasive species legacies (section "Unwanted Legacy Effects From Invasive Species"), plant hydrologic needs (section "Hydrologic Considerations for Seeds and Seedlings"), and the importance of microtopography (section "Microtopography").…”
Section: Figure 6 | (A)mentioning
confidence: 99%
“…Here we address several considerations for preparing a wetland for revegetation. Prior to these actions, appropriate site manipulations are imperative, such as surface contouring and excavation of sites to expose seed banks; removal of subsurface drainage tiles and plugging of drainage ditches to restore hydrology; management of invasive species to alleviate biotic pressures; improving soil conditions through additions of topsoil, organic matter, mulch, lime (to raise pH), fertilizers (if nutrient impoverished), and carbon (if nutrient enriched); inoculation with soil microbes; and soil ripping, disking, or tilling to overcome soil compaction (Galatowitsch and van der Valk, 1994;Vivian-Smith and Handel, 1996;Boyer and Zedler, 1998;Allen et al, 2001;Holguin et al, 2001;Anderson and Cowell, 2004;Daniels et al, 2005;Sutton-Grier et al, 2009;Larson et al, 2019;Scott et al, 2020). We focus here on the next steps following site manipulation: removal of invasive species legacies (section "Unwanted Legacy Effects From Invasive Species"), plant hydrologic needs (section "Hydrologic Considerations for Seeds and Seedlings"), and the importance of microtopography (section "Microtopography").…”
Section: Figure 6 | (A)mentioning
confidence: 99%
“…(Maietta et al 2020) observed that respiration rates were higher in a sandy loam soil compared to a silty clay, with and without 3.3% & 23% wetland hay. Our study showed that coarse grain soils are more vulnerable to SOC loss via CH4 production, which may be one reason why they are generally lower in SOC (Scott et al 2020).…”
Section: Discussionmentioning
confidence: 64%
“…In saturated soils root residues of wetland plants contain suberin and cutin (Watanabe et al 2013), which persist reducing biogenic gas production (Mikutta et al 2006). Organic amendments are more representative of above-ground material, and studies suggest they are less amenable to soil C stabilization compared to natural plant inputs and may produce CH4 (Scott et al 2020).…”
mentioning
confidence: 99%
“…A wetland can be defined as land subject to excessive wetness, to the extent that the wet conditions influence the possible land uses (Sadeghi SH, Hazbavi Z, Harchegani MK (2016).). Wetlands are characterized by the presence of wetland hydrology, hydrophytic vegetation, and hydric soils (Honggen Zhu et al 2016), and are complex ecosystems that are poorly understood relative to terrestrial and aquatic systems (Andrew H. B., et al 2020). Wetlands are frequently transitional landscapes between terrestrial and aquatic systems and therefore possess characteristics of both.…”
Section: General Characteristics Of a Wetlandmentioning
confidence: 99%
“…The dry season interval is long enough to permit successful cultivation of shortseason or medium-season arable crops such as maize, cowpea, okra, melon, watermelon, water-leaf, pumpkin, garden egg, pepper and groundnut (Andrew H. B., et al 2020). Long growing season crops such as yams and cassava are grown on mounds constructed by heaping the surface soil, but are usually harvested early (7 to 8 months) and immature to avoid damage or total crop loss due to flooding.…”
Section: Proceedings Of the Annual Conference Of The Agricultural Extmentioning
confidence: 99%